Electricity generation and winery wastewater treatment using silica modified ceramic separator integrated with yeast-based microbial fuel cell - Michu, Panisa; Chaijak, Pimprapa (Communications in Science and Technology, 2022)
The ceramic separator has been interested in low-cost alternative proton exchange membranes in a microbial fuel cell (MFC). In this study, the silica-modified ceramic separator has been integrated with the yeast-based MFC for electricity generation and phenol treatment from the winery wastewater. The 30% (w/w) silica powder was mixed with the 70% (w/w) natural clay. The modified ceramic plates (0.2, 0.5, and 1.0 cm of thickness) were prepared at 680°C and used for MFC operation. As an anolyte, synthetic winery wastewater (2,000 mg COD/L and 100 mg/L phenol) with 5% (v/v) ethanol was used. The ethanol-tolerant yeast Pichia sp. ET-KK was used as an anodic catalyst. The results showed the maximal power density of 0.212 W/m2 and phenol removal of 95.05% were reached from the 0.2-thick ceramic plate integrated MFC. This study demonstrated that the silica-modified ceramic separator has a high potential for enhancing electricity generation in the yeast-based MFC.